High throughput sequencing data reveals the complete mitogenome, abundance, maternal phylogeny, and mitogenomic diversity of Alectoris chukar of Iraq - Yousif, Paiman; Taha , Hevidar (Emirates Journal of Food and Agriculture, 2023)
Alectoris chukar is a wild game bird found in the north of Iraq, near the center of domestication and diversity of species. The mitogenome is one of the most vital resources for comprehensive studies of genetic diversity and molecular evolutionary relationships among avian species. In this study, we used whole genome sequencing raw reads and bioinformatics analysis to sequence and assemble Alectoris chukar's complete mitogenome for the first time. We also studied the maternal lineage and phylogenetic position of Alectoris chukar, as well as some mitogenomic diversity parameters. As a result, the complete mitogenomes with a length ranging from 16686 bp to 16688 bp of four individuals of wild Alectoris chukar were sequenced and assembled. They have a typical avian mitogenome structure with 2 ribosomal RNA (rRNA), 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, and one non-coding control region. Our findings from bioinformatics analysis remarkably demonstrated that copies of the mitogenome are more abundant in liver tissues than in blood and in the liver tissues of females than in males. The results of phylogenetic analysis clustered the studied mitogenomes with Alectoris chukar as a monophyletic clade. Moreover, in comparison to the different genera, Alectoris chukar showed a high level of mitogenomic similarities to the snowcock species of the genus Tetraogallus within the Phasianidae family. However, they were more distant from other partridges. Additionally, a high percentage of mitogenomic pairwise identities within Iraqi Alectoris chukar and high mitogenomic variations compared to Chinese populations were discovered. The number and location of polymorphic sites indicated that the majority of the mitogenome sequences were conserved, with the control region, ND5, and CYTB genes having the most polymorphic sites. Analyses of phylogenetic and mitogenomic diversity revealed that samples of Alectoris chukar from Iraq have a unique maternal lineage and mitogenomic diversity specific to their geographic distribution, suggesting an Alectoris chukar kurdestanica subspecies. The molecular findings presented here provide valuable knowledge and mitogenomic resources into the evolutionary relationships of Alectoris chukar from the Middle East to avian species in the Phasianidae family. Key words: DNA sequencing; Mitochondrial genome; Partridges; Phasianidae; Phylogeny